Photostabilization of polyvinyl chloride by some new thiadiazole derivatives - Nief, Olfat Abiad (European Journal of Chemistry, 2015)
(5-Amino-1,3,4-thiadiazole-2-yl)phenol and it derivatives have been synthesized and characterized by spectral methods lik (FT-IR, UV-Vis, and 1H NMR) and elemental analysis beside the measurements of their physical properties. All the prepared compounds were used as photo stabilizer with polyvinyl chloride. The rate of photo degradation and photo stabilization for PVC films were monitored with irradiation time by measuring the carbonyl (Ico) index values. In addition, the effect of concentrations additives on the rate of photo degradation and photo stabilization process was also studied. We found that the rates were increased with increasing of additives concentrations. Besides, the effect of film thickness is studied and the results showed that the increasing of film thickness will decrease the rate of photo degradation as the following sequences: [5] > [2] > [1] > [3] > [4] > PVC. Degree of deterioration (α), average number of cuts per single polymer chain (s), were calculated for PVC films as a control and that which contains the additives. According to the experimental results obtained several mechanisms were suggested depending on the structure of the additive. Among then UV absorption and radical scavenger for photo stabilizer additive mechanisms were suggested.